2024
DOI: 10.1249/mss.0000000000003411
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of “Super-Shoes” and Foot Strike Pattern on Metabolic Cost and Joint Mechanics in Competitive Female Runners

EDUARDO MARTINEZ,
WOUTER HOOGKAMER,
DOUGLAS W. POWELL
et al.

Abstract: “Super-shoes” are designed to improve endurance running performance by reducing the metabolic demands of running. While the research on “super-shoes” is still developing and has mostly been studied in male runners, it is not clear how possible mediating factors, such as foot strike pattern, influence the metabolic cost and joint mechanics in competitive female runners. Purpose To assess the influence of “super-shoes” on metabolic cost and joint mechanics in competitive female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Specifically, Barnes and Kilding (37) reported running economy benefits of between 1.7% and 7.2% when highly trained runners used AFT, however differences between males and females were trivial to small across conditions. Most recently, Martinez and colleagues (38) reported metabolic power improvements of 4.2% and running economy improvements of 3.9% when trained female runners ran in AFT compared to control shoes, which is consistent with findings in males (15). Contrary to these initial findings, women have unique running injury profiles (39), specific running biomechanics (40), as well as unique energetics and fatigue dynamics during running when compared to men (41,42).…”
Section: What Does the Current Evidence Suggest And What Should Futur...supporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, Barnes and Kilding (37) reported running economy benefits of between 1.7% and 7.2% when highly trained runners used AFT, however differences between males and females were trivial to small across conditions. Most recently, Martinez and colleagues (38) reported metabolic power improvements of 4.2% and running economy improvements of 3.9% when trained female runners ran in AFT compared to control shoes, which is consistent with findings in males (15). Contrary to these initial findings, women have unique running injury profiles (39), specific running biomechanics (40), as well as unique energetics and fatigue dynamics during running when compared to men (41,42).…”
Section: What Does the Current Evidence Suggest And What Should Futur...supporting
confidence: 78%
“…Notably, the only studies which have reported female-specific data regarding the influence of AFT on running economy indicate that there is no significant sex-based advantage ( 37 , 38 ). Specifically, Barnes and Kilding ( 37 ) reported running economy benefits of between 1.7% and 7.2% when highly trained runners used AFT, however differences between males and females were trivial to small across conditions.…”
Section: Introductionmentioning
confidence: 99%